Theodore Roosevelt an autobiography by Theodore Roosevelt - Roosevelt, Theodore, 1858-1919 (Open Road Media, 2016)
The firsthand account of the life of adventurer, scholar, war hero, and twenty-sixth president of the United States Theodore Roosevelt. There must be the keenest sense of duty, and with it must go the joy of living. Here, in his own words, Theodore Roosevelt recounts his remarkable journey from a childhood plagued with illnesses to the US presidency and beyond. With candor and vivid detail, this personal account describes a life guided by a restless intelligence, a love for adventure, and an unflagging duty to his country. Roosevelt sheds light on his wide array of roles, from New York police commissioner, where he waged a battle against corruption, to cattle rancher in the Dakotas to assistant secretary of the US Navy under William McKinley to leader of the legendary Rough Riders at the outbreak of the Spanish-American War, when he led the 1st United States Volunteer Cavalry to victory in the Battle of San Juan Hill. These extraordinary accomplishments earned Roosevelt national fame and set the stage for his ascent to the White House. As twenty-sixth president of the United States, he ushered in the Progressive Era with his domestic policies, such as the Square Deal, and trust-busting of monopolies, such as Standard Oil. He was a war hero, scholar, statesman, adventurer, and Nobel Peace Prize winner. Theodore Roosevelt: An Autobiography provides unique insight into the truly remarkable life of one of America's most beloved presidents. This ebook has been professionally proofread to ensure accuracy and readability on all devices.